USING RASCH MODEL TO UNDERSTAND PSYCHOMETRIC PROPERTIES OF JUNIOR STUDENTS AGGRESSIVE BEHAVIOR INVENTORY (J-SABI) - Yuda Syahputra; Stefanus Soejanto Sandjaja; Alizamar Alizamar; Afdal Afdal; Lira Erwinda (Universitas Gunadarma, 2022)
The emergence of aggressiveness among students requires attention from various parties, especially schools. The direction of this research is to develop and examine the validity of the Junior Students Aggressive Behavior Inventory (J-SABI), to know the level of suitability and item’s difficulty level, also to know the variable maps of the person’s ability to answer an item’s ability to describe aggressive behavior. The sample of this study consist of 360 with the number of items was 47. The analytical technique that used was Rasch model to examine the reliability, instrument validity, item’s validity, the function of differential items, and the validity of the ranking scale. The result shows that overall inventory which developed was valid and reliable (person reliability consist of 0.89 and item reliability 0.98). The validity of the instrument respondents using variable maps show the Item P15 is a matter of the highest difficulty level (+0.69 logit), which means the probability of all the students to work on this matter right is small. As for the P52 is a matter that almost all students can work properly, logit value is low (-0.80 logit). The value of Andrich Threshold moving from option 1 (none), then to the second choice (logit -0.50), option 3 (-0.30 logit), selection 4 (-0.19), and the option 5 (+1.00 logit), indicates the five choices answer given are valid for respondents